On the Integration Management of Companies and the Institutions of Higher Education - Spivakovskiy, O.V. (Journal of Information Technologies in Education (ITE), 2009)
This article examines the necessity of business and universities integration under the conditions of uncertainty of entrepreneurial environment in Ukraine. There are certain contradictions between the needs of real business and competences produced by universities. In order to overcome these drawbacks the research was done focused on the ways and mechanisms of changing this situation to more adequate reaction to the labor market requirements.